FRANCHISING IN TOURISM ON EXAMPLE OF THE TUI TRAVEL AGENCY - Kacprzak, Marzena; Mikulska, Teresa (Acta Scientiarum Polonorum. Oeconomia, 2008)
The article presents issues connected with franchising, as one of methods having impact on the tourism market development. Franchising systems combine advantages of a large enterprise with merits of small enterprises, excluding their flaws. Franchising networks are able deliver standard services of an equal quality, they can advertise not only in their own region, they can diagnose changes of customer’s preferences and regional differences earlier and react to them in a suitable way. A subject of research was the TUI Travel Office.